Automobile Paint Reducer Induced Acute Kidney Injury: A Case Series (Journal of Renal and Hepatic Disorders, 2021)
The various aspects of the automobile industry also carry with it the risk for occupational health hazards with it. Toluene has also evolved as a commonly used drug by substance abusers. Accidental exposure or self-poisoning with these substances has been reported in literature. These substances can also cause distal renal tubular acidosis (RTA), acute tubular necrosis, glomerulonephritis and interstitial nephritis, rhabdomyolysis and myoglobinemia.In this series, we report about three patients who developed renal manifestations because of organic solvents. Two of the three patients had ingested the paint reducer substance and the third one was addicted to sniffing the toluene based paint reducer. All the patients had in taken these substances s with suicidal intent and developed acute kidney injury (AKI) and severe metabolic acidosis. One of the patients had features of rhabdomyolysis as well. The third patient was a substance abuser and had inhaled higher than usual dose and developed severe and refractory acidosis and mild kidney injury and required Renal Replacement Therapy (RRT) for acidosis. All the patients eventually recovered their kidney functions and were doing well during their follow-up.Toluene based organic solvents lead to acute neurological symptoms, accompanied by severe metabolic alterations, organ injury and dysfunction. An association of the development of hypokalemic paralysis and metabolic acidosis with toluene intoxication has been observed. The management of acute toluene toxicity is mainly conservative, consisting of electrolytes correction, acid-base and fluid abnormalities and renal replacement therapy in severe AKI.Organic solvent exposure may result in acute tubular necrosis, rhabdomyolysis, RTA and AKI irrespective of the intake route. Clinical suspicion of organ dysfunction and failure and timely induction of supportive care leads to a good outcome.
Keywords: Acute kidney injury; organic solvent; paint reducer; toluene